Dual-Isotope SPET201T1 Rest/99mTc-MIBI Stress: One-Day Protocol for Pre-Operative Myocardial Imaging? - Fikrle, A.; Rösler, H.; Ritter, E. P.; Lüscher, D.; Ledermann, H.; Berthold, Th. (Nuklearmedizin - NuclearMedicine, 1994)
We compared the results of a rest 201TI/stress 99mTc-MIBI protocol, both by means of separate single isotope and simultaneous dual isotope acquisition, with a standard stress/rest 99mTc-MIBI 2-day protocol in 11 patients with low probability of CAD and 14 patients with chronic CAD. In patients with CAD 406 segments (sgs) were analysed. In the standard protocol 119sgs were classified as pathological of which 50.4% were fixed and 49.6% reversible defects. With the MIBI-stress/TI-rest single 33% of 119 pathological sgs were fixed and 67% reversible defects. With the MIBI-stress/TI-rest dual only 20% were fixed and 80% reversible defects. The reversibility of 59 MIBI-stress/ MIBI-rest reversible defects was quantified: MIBI-stress/MIBI-rest 35 ± 16% MIBI-stressl-rest single 50 ± 26% and MIBI-stress/TI-rest dual 48 ± 22%. The results of 99mTc-MIBI rest and 201TI rest studies in patients with chronic CAD are not the same. Dual-isotope 1-day 201TI-rest/99mTc-MIBI-stress SPET data, acquired separately, may give fast and complete information on myocardial perfusion at stress and rest, respectively, and on myocardial viability.Wir haben die Ergebnisse eines Eintags-Protokolls mit 201TI in Ruhe und 99mTc-MIBI unter Belastung - jeweils nach Ein- oder Zweikanal-Akquisition - mit einem Standard-Vorgehen über 2 Tage (Belastung und Ruhe mit MIBI) bei 11 Patienten mit niedriger KHK-Wahrscheinlichkeit und 14 mit chronischer KHK verglichen. Unter 406 sgs bei Patienten mit KHK waren in MIBI-Belastung/MIBI-Ruhe 119 sgs pathologisch, davon 50,4% mit fixem und 49,6% mit reversiblem Defekt. Dagegen fanden sich mit MIBI-Belastung/TI-Ruhe (single) jeweils 33% und 67%, in dualer Akquisition sogar nur 20% fixe, aber 80% reversible Defekte. Das Ausmaß der Umverteilung (59 reversible Defekte MIBI-Belastung/MIBI-Ruhe) wurde quantifiziert und betrug (in %) für MIBI-Belastung/MIBI-Ruhe 35 ± 16, für MIBI-BelastungATI-Ruhe (single) 50 ± 26 und (dual) 48 ± 22. Die Ergebnisse der Ruhe-Untersuchungen sind bei chronischer KHK nicht identisch mit 99mTc-MIBI und 201TI. Das 1-Tag-Protokoll 201TI in Ruhe und 99mTc-MIBI unter Belastung gibt, wenn in separaten Photo-Peaks gemessen werden, komplette Information über die myokardiale Durchblutung in Ruhe bzw. unter Belastung und über die myokardiale Viabilität.
Keywords: Myocardial perfusion; myocardial viability; SPET